Analisis Kinerja Fasilitas Trotoar Bagi Pejalan Kaki Di Kota Banjarnegara - Anindya Lukita; Sulfah Anjarwati (UM Purwokerto Press, 2026)
This study aims to analyze the performance of pedestrian facilities along Let. Jend. Suprapto Street in Banjarnegara City using the Level of Service (LOS) method, which emphasizes pedestrian volume, flow rate, speed, density, and available walking space to ensure comfort and safety. A descriptive quantitative method was employed to identify the types of sidewalk facilities and evaluate their performance. The findings revealed physical damage in the northern and southern segments of the sidewalk, including broken tiles and landslides caused by fallen trees. These damages compromise pedestrian comfort and safety. The overall condition of the sidewalk is still inadequate, particularly in terms of supporting infrastructure such as speed control devices, guardrails, seating areas, bicycle parking, surveillance cameras, emergency boxes, and signage. Existing facilitiesincluding traffic signs, road markings, street lighting, shelters, green lanes, and bus stops (particularly in the southern segment) require maintenance and repair. Based on performance analysis, the Level of Service (LOS) for pedestrian speed, average speed, density, and effective walking space was categorized as